Plant Cell wall polysaccharides: immunomodulators of the immune system and source of natural fibers - (:unkn) unknown (My University, 2011)
The greatest part of the world’s population relies on plants as its source of medicines. The crude vegetable drugs or their extracts are utilized, primarily by lay persons either as a form of ‘alternative’ therapy for the treatment of diseases often of a chronic nature or to attain or maintain a state of improved health. While western developed countries have turned their efforts to promoting and developing a worldwide chemical and pharmaceutical industry, most of the southern countries, including African ones, have neglected their ethnobotanical legacy. Nowadays, the economic crisis and the high costs of most of the modern pharmaceutical based treatments have enhanced a come-back to secular and indigenous medicines. Starting from herbal teas to the development of sophisticated therapies based on plant decoctions or well-purified phytochemical compounds, plant-derived components have been proven to be effective in the prevention or treatment of skin-related pathologies, cancers, metabolic diseases such as obesity and diabetes. These secular treatments include body-washes, decoctions, massages, ingestions, etc.... The aim of this review article is to describe plant-derived cell wall polysaccharides shown to exhibit biological activities. If better characterized, studied and valorised, they may play an important role in health care policy in the world, and more particularly in numerous developing countries in the next decades.
Keywords: African Research